2017
DOI: 10.19030/jabr.v33i3.9936
|View full text |Cite
|
Sign up to set email alerts
|

Matching Level And Investors’ Heterogeneous Beliefs

Abstract: This study investigated the relation between matching level and investors' heterogeneous beliefs using listed firm (KOSPI) data in Korea.This study is based on prior research that reported that the higher the matching level, the less the noise included in accounting earnings and the higher the earnings quality. Karpoff (1986), Bamber (1987, Ajinkya, Atiase, & Gift (1991) and Dormeier (2011) According to microeconomics theory of Mas-Colell, Whinston, and Green (1995)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Therefore, Paek [3] explains that a poor matching level leads to low quality of earnings. Based on the logic that a low matching level lowers the quality of earnings, Lee and Jung [8] and Jung and Moon [6] approved that a poor matching level decreases the future earnings response coefficient (FERC) and increases the trading volume.…”
Section: Research Related To Matching and Establishment Of Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, Paek [3] explains that a poor matching level leads to low quality of earnings. Based on the logic that a low matching level lowers the quality of earnings, Lee and Jung [8] and Jung and Moon [6] approved that a poor matching level decreases the future earnings response coefficient (FERC) and increases the trading volume.…”
Section: Research Related To Matching and Establishment Of Hypothesesmentioning
confidence: 99%
“…Firms with a high proportion of private debt are most likely to make transactions with specific banks, and since these banks have long-term relationships with these firms, it has been confirmed that access to internal corporate information is easy [1][2][3]. Banks, which are private debt creditors, have easy access to corporate monitoring as well as access to private information [4][5][6]. As a result, Chun, et al [7] found that the higher the private debt ratio, the lower the benefit of accounting information reliability and an increase in the manager's opportunistic earnings management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that high earning's quality can be a factor in reducing investors' heterogeneous beliefs. In this regard, Jung and Moon (2017) explain that high matching increases earning's quality and decreases investors' heterogeneous beliefs. Kim et al (2012) report that CSR activities contribute to enhancing transparency and reliability of net income.…”
Section: Setting Factors Affecting Investors' Heteroge-mentioning
confidence: 99%
“…Prior studies related to investors' heterogeneous beliefs have reported that a high earning's quality and a low level of information asymmetry reduce an investor's heterogeneous beliefs for target companies (Ajinkya et al, 1991;Jung & Moon, 2017;Ziebart, 1990). In addition, prior studies related to investors' heterogeneous beliefs analyzed the relationship between various firm-specific variables and investors' heterogeneous beliefs.…”
Section: Introductionmentioning
confidence: 99%